Palatal masticatory soft-tissue thickness and its relation to skeletal profile and palatal depth: a clinico-radiographic study - Dhawal Mody; Vaishnavi Biradar; Vrushali Lathiya; Abhay Kolte (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: Skeletal profile plays a significant role in craniofacial morphology and may alter the spatial positioning of anatomical structures. The palatal mucosa is used for free grafts in periodontics to surgically treat specific alveolar ridge deficiencies through various ridge augmentation techniques, as well as to increase the width of keratinized gingiva in dentate patients. Purpose: To evaluate palatal masticatory soft-tissue thickness and its relation to skeletal profile and palatal depth. Methods: Ninety systemically and periodontally healthy Indian patients, aged 18 to 50 years, were enrolled in the study. Ninety lateral cephalograms were taken and divided into three groups: brachyfacial (30), mesofacial (30), and dolichofacial (30). Bone sounding was carried out under local anesthesia at 24 defined anatomical sites, and palatal depth was calculated by using a vernier caliper directly on the palate. Results: With an average thickness of 2.0 to 4.06 mm, at 11 mm, there were noticeably more males than females in the group. In brachyfacial patients, there was no significant shift in the palatal thickness at 3 mm and 7 mm between genders. Palatal depth was greatest in dolichofacial patients and least in brachyfacial patients. Conclusion: There is a positive correlation between skeletal profile and palatal soft-tissue thickness in dolichofacial patients, and there is no significant difference in palatal soft-tissue thickness between male and females; however, at 11 mm in male brachyfacial patients, a significant difference is present. Even in younger individuals, subepithelial connective tissue grafts can be harvested in sufficient volume to meet the requirements of grafting procedures.